The The Influence Of Corporate Governance On Profitability With Sustainability Report As A Moderation In The Coal Mining Sector: Pengaruh Tata Kelola Perusahaan Terhadap Profitabilitas dengan Laporan Keberlanjutan Sebagai Moderasi pada Sektor Tambang Batubara - Yashinta Happy Msutika Utami,; Stephana Dyah Ayu Ratnaningsih, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the effect of Corporate Governance on profitability in coal mining sector companies listed on the Indonesia Stock Exchange. The population in this study was in 2018-2022. The purpose sampling method was used in this study to see the number of companies observed, which was 230 companies. The statistical method used to test the hypothesis is moderating regression analysis. Before conducting the regression, the hypothesis was tested using classical assumptions. The results of the study indicate that corporate governance (IC) has a significant effect on profitability with the sustainability report as a moderating variable.